Effects of HPEM stress on GaAs low-noise amplifier from circuit to component scale. (September 2018) - Girard, M.; Dubois, T.; Hoffmann, P.; Duchamp, G.
Abstract: This paper presents a study of High Power Electromagnetics (HPEM) stress effects on a GaAs (Gallium Arsenide) low-noise amplifier (LNA). This work aims to evaluate such electrical stress effect from circuit to component scale in relation to more general Intentional electromagnetic interference (IEMI) studies. Conducted susceptibility measurements were made on a specifically designed device under test (DUT). Those experiments yielded interesting results concerning exposition of the DUT to destructive values of interference power, as well as its response to non-destructive but significant powers. The destruction process has been analyzed using time-domain and frequency-domain measurements. Highlights: GaAs p-HEMT low-noise amplifiers are vulnerable to reasonable amounts of power. Destruction mechanism was investigated with electrical and physical analysis. Device can be degraded by HPEM pulses, partly explained by trap creation.